Khilāfah in the View of Nahdhatul Ulama (NU), Muhammadiyah, and Nahdhatul Wathan (NW) Ulema in Lombok - Musawar Musawar; Gatot Suhirman (Al-Jami'ah Research Centre, 2021)
Indonesia is a multiethnic and religious state anchored in the five state principles, Pancasila and the 1945 Constitution. However, its stability has recently been disrupted by the emergence of khilāfah propagated by the banned Islamic organization, the Hizb al-Tahrir Indonesia (HTI). The concept of khilāfah proposed by the organization violates against the state’s ideology of Pancasila. Such a phenomenon is of paramount importance to examine. Hence, this qualitative study aimed to explore the concept of khilāfah from the perspectives of Islamic ulema from the three prominent Islamic mass organizations, the biggest mass organination, Nahdhatul Ulama (NU), Muhammadiyah, and Nahdhatul Wathan (NW) on the island of Lombok. Drawing on the data garnered from the observation, interviews, and documentation that analyzed suitable with its’ substation of the writing. Finally, the findings of this writing showed that the three Islamic mass organizations generally denied khilāfah as a state system. NU firmly rejected the khilāfah system because it more likely pertained to extremism. For the same token, Muhammadiyah denied the concept, but welcomed it as a culture, while NW opposed it as being contradictory to the republic in that khilāfah belongs to the empire system.[Indonesia merupakan negara multietnik dan agama yang dinaungi oleh Pancasila dan UUD 1945. Namun stabilitasnya sempat terganggu dengan kemunculan wacana khilafah yang dipropagandakan oleh HTI. Konsep khilāfah ini yang kemudian diperhadapkan dengan ideologi Pancasila dan menjadi fenomena yang penting untuk dielaborasi. Dalam artikel ini akan mengeksplorasi konsep khilāfah ulama dari tiga organisasi massa Islam, NU, Muhammadiyah dan NW di Lombok. Berdasarkan data yang dikumpulkan melalui observasi, wawancara dan arsip menunjukkan bahwa tiga ormas Islam tersebut menolak khilāfah sebagai sistem negara. NU menolaknya karena cenderung mirip dengan ekstremisme. Muhammadiyah juga menolaknya sebagai sistem tetapi masih bisa menerima sebagai budaya. Sedangkan NW menolaknya karena kontradiksi dengan sistem republik dan mirip dengan sistem kerajaan.]